Can the treatment duration be shortened in bismuth-containing therapies for Helicobacter pylori eradication? - Özer Etik, Diğdem; Sezer, Semih; Suna, Nuretdin; Öztaş, Erkin; Kılıç, Zeki Mesut Yalın (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The duration of Helicobacter pylori (H. pylori) eradication therapy as a range (e.g., 10–14 days) is an ignored problem. There is no any particular treatment duration described in current guidelines, and the conditions for when to use 10-day therapy vs. 14-day therapy have not been elucidated. The aim of this study is to determine an effective and reliable H. pylori treatment duration in clinical practice. There were four different treatment modalities administered to groups, and success rates were compared. Materials and Methods: Patients were eligible to participate in the study if they had a biopsy-proven H. pylori infection. Each patient was randomly assigned to one of the four treatment groups according to a predetermined sequence: 14-day or 10-day bismuth-containing quadruple therapy (BQT) groups and 14-day or 10-day moxifloxacin-bismuth-combined treatment (MBCT) groups. Results: A total of 216 patients (54 per group) were enrolled. Two-hundred six patients (95.3%) completed therapy. There was no significant difference in the eradication rates between those patients who received 10- and 14-days BQT regimens (p=0.67). The 14-BQT protocol had the highest eradication rate, the MBCT regimes had the highest compliance, and the 10-MBCT protocol had the poorest results for H. pylori eradication. The posttreatment questionnaire on adverse effects identified nausea/vomiting as the most common side effect (35.7%). Conclusion: Overall, the results of our study suggest that shortening the BQT protocol duration to 10 days does not weaken the H. pylori eradication rate. Moreover, quinolone-containing therapies with the lowest eradication rate among the groups should not be offered as a salvage treatment in case of the BQT failure.